Phosphorylation of the cap-binding protein eIF4E by the MAPK-activated protein kinase Mnk1 - Pyronnet, Stéphane (Biochemical pharmacology, 2000)
The purpose of this review is to summarize recent experimental data describing the regulation of the phosphorylation of eIF4E, the cap-binding protein, by the MAPK-activated protein kinase Mnk1. Mnk1 does not interact directly with eIF4E, but uses a docking site in eIF4G, a partner of eIF4E. Consequently, control of eIF4E phosphorylation may not strictly depend on changes in Mnk1 activity. The possibility that integrity of the eIF4E/eIF4G/Mnk1 complex also impinges upon eIF4E phosphorylation is discussed.